Flowering response and crop duration of aromatic rices in diverse environments. - Shahidullah, S. M.; Musa, Mohamed Hanafi; Ashrafuzzaman, M.; Salam, M. A.; Khair, A. (Elsevier, 2009)
Crop duration of a rice plant, essentially dictated by flowering response, is an important selection criterion. It is determined by the interaction of genotype and environment. A field experiment was conducted with 40 rice genotypes to assess the fluctuation and/or stability of crop duration in a series of 16 environmental conditions. The effects of genotype, environment and all the components of G×E interaction were highly significant. Among the genotypes Benaful and Gandho kasturi were most sensitive to environmental changes, and indicating lower adaptability over the environments. Crop durations of 17 genotypes were comparatively stable against environmental changes. Four genotypes viz. Basmati PNR346, BR28, Neimat and Sarwati showed only nonlinear sensitivity and thus unpredictable fluctuation. Seventeen genotypes indicated average stability over the environments. The AMMI analysis identified Badshabhog, Basmati Tapl-90, Bhog ganjia, BR38, Elai, Jata katari and Radhuni pagal as most stable genotypes over the environment series. It also advocated three comparatively stable environments for all the genotypes.